PERANCANGAN MEJA KERJA DAN PENYANGGA KOMPONEN MOTOR PADA UKM SBS GARAGE AND PAINT - Siahaan, Bobby Bernard; Sirait, Ganda (LPPM Universitas Putera Batam, 2023)
The growth of the automotive world is growing rapidly, based on data from the Central Statistics Agency (BPS), the number of motorized vehicles in 2021 will reach 120,042,298 units. The increasing number of vehicles affects the volume on the road resulting in the risk of accidents. This can cause the vehicle to become scuffed and damaged. Based on this description, this provides a business opportunity for the paint shop. SBS Garage and Paint UKM is a business engaged in motorcycle painting services. There are problems in painting, namely the positioning of motor components when painting does not use ideal tools resulting in the fall of motor components when laying and painting, during the painting process, the painter must change positions for painting on different component sides, so a table design is needed work and support for motor components so that the Painter is comfortable during the painting process so that it becomes more optimal. Identification of needs and design using the NIDA method (Need, Identification, Decision, and Action). Researchers made 2 alternative results of the design of the workbench and support. Based on the design selection analysis, the selected workbench design is alternative 1 because the height can be adjusted and the support design chosen is alternative 1 because it can move components without removing the support first. After designing the workbench and support components, painting can be done more optimally.